Quality of coffee seeds after retardment of post-harvest processing - Caixeta, Ivan Franco; Guimarães, Renato Mendes; Malta, Marcelo Ribeiro (Coffee Science - ISSN 1984-3909, 2014)
The routine procedure of coffee seed production is based on the pulping of fruits immediately after the harvest of the cherry fruit to prevent fermentation and possible damage to the seed quality. However there are arguments of testers of natural special coffees (with husk during the drying up), that this procedure leads to full-bodied, sweet beverage, with moderate acidity. The present study was conducted with the objective to verify possible changes in coffee beans due to husk permanence and from mucilage to peeling. The selective harvest of 500 litres of cherry coffee fruits was conducted at the EPAMIG Experimental Farm, in Machado - MG, in the cultivar Topazio MG 1190. The procedure followed the company rules for bean production. The fruits harvested were divided into 10 batches of 50 litres. The fruits of the lot 1 (treatment 1) were pulped and peeled immediately and then returned to the shade drying. The remaining batches (treatments) were processed after every 24 hours, continuing to dry shade. After the bean drying process , were evaluated the following variables: bean moisture content, total acidity, reducing sugars, non-reducing sugars, total sugars, total polyphenols, polyphenoloxidase activity, color index, electrical conductivity, potassium ions leaching, germination, emergence and sensory analysis. The results indicated that the permanence of the peel and fruit mucilage of coffee until the seventh day after the harvest does not affect the quality of bean.